Downregulation of ICCs and PDGFRα+ cells on colonic dysmotility in hirschsprung disease - Gu, Aiming; Wu, Zhihao; Wang, Peng; Liu, Jun; Wang, Jianfeng; Wang, Qianqian; Chen, Jie (Frontiers in Pediatrics, 2023)
Background: To investigate the effect of the distribution and expression of interstitial cells of Cajal (ICCs) and platelet-derived growth factor receptor-α positive (PDGFRα+) cells in different colon segments on colonic motility in children with Hirschsprung disease (HSCR). Methods: Smooth muscles of the narrow and dilated segments of the colon were obtained from 16 pediatric patients with HSCR. The proximal margin was set as the control section. The mRNA and protein expressions of c-Kit, PDGFRα, ANO1, and SK3 channels were examined. Circular smooth muscle strips of the colon were prepared for performing electrophysiology experiments using electric field stimulation (EFS) and intervention from different drugs (TTX, NPPB, Apamin, L-NAME, and CyPPA). Results: The mRNA and protein expressions of c-Kit, ANO1, PDGFRα, and SK3 were much lower in the narrow segment than those in the dilated and proximal segments of the colon. The narrow segment showed a considerably spontaneous contraction of the muscle strip. After the EFS, the relaxation response decreased from the proximal to the narrow segment, whereas the contraction response increased. TTX blocking did not cause any significant changes in the narrow segment. In contrast, when NPPB, Apamin, L-NAME, and CyPPA were used to intervene in the muscle strips, the proximal segment showed a more sensitive inhibitory or excitatory response than the narrow segment. Conclusions: Downregulation of the ICCs and PDGFRα+ cells from the proximal to narrow segment may be responsible for the dysmotility of the colon in pediatric HSCR.